Developing a Culture of Reading Literacy Through Reading Corner For Grade III Students at SDK Joge - Palu, Maria Fatima; Ita, Efrida; Nafsia, Andi; Meka, Marsianus (Universitas Muhammadiyah Ponorogo, 2025)
The purpose of this study is to foster a culture of reading literacy through a reading corner for students in grade III of SDK Joge. This type of research is a qualitative descriptive study. The subjects of this study were 11 students in grade III of SDK Joge. The data collection methods used in this study were observation, interview, and documentation methods. The data in this study were analyzed using the Milles and Huberman model data analysis technique consisting of 1) data collection. 2) data reduction, 3) data integration, and 4) concluding. The results of this study indicate that after reading literacy activities, students experienced changes, namely, initially, they were only able to recognize letters when literacy activities were held, and students were able to move up to the next level to read words. Students who were only able to read by spelling after literacy activities were able to read fluently. Thus, it can be concluded that through student reading aloud activities, students read books in groups and discuss readings can foster a culture of reading literacy in grade III students at SDK Joge.